Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1129729820971533
|View full text |Cite
|
Sign up to set email alerts
|

Implanted blood vessel external support device (VasQ™) for creation of hemodialysis arteriovenous fistula: A single-center experience

Abstract: Introduction: the external support device VasQ is intended to promote arteriovenous fistula (AVF) maturation by maintaining the optimal anastomotic angle in order to minimize blood flow disturbances around the anastomotic area. The aim of the study is to assess efficacy and safety of the VasQ device both in brachiocephalic and radiocephalic fistulae. Methods: a single institution prospective study was conducted with implantation of the VasQ device during AVF creation. Clinical and Doppler ultrasounds evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…By optimizing geometrical configuration of arteriovenous anastomosis, it should lower the wall shear stress and transversal vein oscillations. 17 Literature has largely emphasized the role of mechanical wall shear stress as responsible for endothelial nitric oxide and reactive oxygen species synthesis. This should not only responsible for vein intimal hyperplasia and consequent lack of maturation, but also for matrix metalloproteinase production, vessel wall damage, and vein enlargement under Laplace’s forces.…”
Section: Discussionmentioning
confidence: 99%
“…By optimizing geometrical configuration of arteriovenous anastomosis, it should lower the wall shear stress and transversal vein oscillations. 17 Literature has largely emphasized the role of mechanical wall shear stress as responsible for endothelial nitric oxide and reactive oxygen species synthesis. This should not only responsible for vein intimal hyperplasia and consequent lack of maturation, but also for matrix metalloproteinase production, vessel wall damage, and vein enlargement under Laplace’s forces.…”
Section: Discussionmentioning
confidence: 99%
“…Antistenotic treatment modalities to improve venous remodeling during maturation include perivascular delivery of sirolimus (108), allogeneic ECs (109,110), or pancreatic elastase (111,112), and devices (VasQ, Optiflow) that support the ideal angle of arteriovenous anastomosis (113 117). The latest results on the sirolimus implants are pending (108).…”
Section: Research Models Current Challenges and Pending Questionsmentioning
confidence: 99%
“…The latest results on the sirolimus implants are pending (108). VasQ resulted in high maturation rates in single-arm and retrospective studies (117 119), but mixed results in short-term primary or secondary patency compared with the control arm (114,118,119). The rest are currently not recommended by the Kidney Disease Outcomes Quality Initiative guidelines due to lack of phase 3 studies (Optiflow) or significant benefits in AVF outcomes (ECs, elastase) (15).…”
Section: Research Models Current Challenges and Pending Questionsmentioning
confidence: 99%
“…Recent studies demonstrated the device is safe, and reported improved functional patency for AVFs created using the VasQ TM as compared to AVFs created with conventional surgery. [6][7][8][9][10][11] However, the effect of the device on hemodynamic conditions and its role in regularizing the blood flow have yet to be adequately assessed. We have recently shown that coupling non-contrast enhanced magnetic resonance imaging (MRI) and highresolution CFD provides a promising approach 12 to investigate AVF morphology and hemodynamics, possibly identifying critical hemodynamic conditions that may contribute to AVF remodelling after surgery.…”
Section: Introductionmentioning
confidence: 99%